Nectin4 is a potential therapeutic target for asthma - Lee, Pureun-Haneul; Choi, Seon Muk; An, Min Hyeok; Hwang, Da Yeon; Park, Shinhee; Baek, Ae Rin; Jang, An-Soo (Frontiers in Immunology, 2022)
Background Nectins comprise a family of cellular adhesion molecules involved in Ca2+-independent cellular adhesion. Neither the biological significance nor clinical potential of Nectin4 for asthma has been investigated. Objectives The aims of this study were to elucidate the role of Nectin4 in airway inflammation and to determine the relationship between Nectin4 and clinical variables in patients with asthma. Methods The relationship between Nectin4 levels in the blood of asthmatic patients and clinical variables was examined. Dermatophagoides pteronyssinus 1 (Der p1)-exposed normal human bronchial epithelial (NHBE) cells, and Nectin4-deficient (Nectin4−/−) and wild-type (WT) mice sensitized/challenged with ovalbumin (OVA), were used to investigate the involvement of Nectin4 in the pathogenesis of bronchial asthma via the Src/Rac1 pathway. Results Plasma Nectin4 levels were significantly higher in asthmatic patients than controls and correlated with specific IgE D1, D2, lung function. The ROC curves for Nectin4 levels differed between asthma patients and controls. Nectin4/Afadin and Src/Rac1 levels were significantly increased in NHBE cells exposed to Der p1, but decreased in NHBE cells treated with Nectin4 siRNA. Airway obstruction and inflammation, as well as the levels of Th2 cytokines, Nectin4, and Src/Rac1, were increased in WT OVA/OVA mice compared with WT sham mice. Nectin4 knockdown resulted in lower levels of Afadin and Src/Rac1 in Nectin4−/−OVA/OVA than WT OVA/OVA mice. Conclusion These results suggest that Nectin4 is involved in airway inflammation and may be a therapeutic target in patients with asthma.